The Correlation of COVID-19 Vaccination With COVID-19 Patient Mortality in Depok City, Indonesia - Nugrahari, Dian; Adisasmita, Asri, Prof; Hamdah, Nurhanifah (Jurnal Epidemiologi Kesehatan Indonesia, 2024)
Vaccination is a disease prevention method recommended by the WHO as it will reduce disease severity, mortality rate and risks. The objective of this study is to discover the impact of COVID-19 vaccination against COVID-19 mortality rate in Indonesia. This was a retrospective cohort research on the data from the NAR COVID-19 database and the KPCPEN COVID-19 Dashboard of the Depok City Health Department from May 2020-February 2023. We performed a Cox proportional hazard analysis to obtain the risk for death. We discovered that COVID-19 vaccination reduced the mortality until it was less than 10% of unvaccinated population (0,24% for vaccinated vs. 2,5% for unvaccinated). We found that vaccination reduced the risk of death for COVID-19 patients to 91% (AHR=0.09; 95% CI = 0.07-0.11; p